Open-source Google Earth Engine 30-m evapotranspiration rates retrieval: The SEBALIGEE system. (November 2020) - Mhawej, Mario; Faour, Ghaleb
Abstract: In this study, an open-source Google Earth Engine-based (GEE) system is proposed, surnamed SEBALIGEE, based on the Surface Energy Balance for Land – Improved (SEBALI) model. SEBALIGEE has the ability to produce monthly EvapoTranspiration (ET) assessments with an automatic fetching of the required inputs, based on satellite datasets already hosted within the GEE platform. Calibrations followed by validations were made in five different countries (i.e. United States, China, Italy, Germany, and Belgium) between 2013 and 2017. It was followed by the application of the SEBALIGEE over a 307 000 km 2 in the plain region in the State of California, United States, between 2017 and 2019. As an average in these selected years, aquaculture appeared to be consuming the largest amount of water with 1109.72 ± 215.07 mm/year. The proposed open-source system aims at improving the assessment of ET and water productivity towards better management of water resources. Highlights: An open-source Google Earth Engine 30-m Evapotranspiration Rates was proposed. Calibrations and validations were made in five different countries between 2013 and 2017. Annual ET rates were assessed for 83 different existent crops' type in California, United States. Shrubland and grassland/pasture accounted for 41.11% of the total consumed water. SEBALIGEE aims at improving the assessment of ET towards better management of water resources.